Pathergy Phenomenon - ERGUN, SAFİYE ATLAS TÜLİN (FRONTIERS MEDIA SA, 2021)
Skin pathergy reaction (SPR) is a hyperreactivity response to needle induced trauma which is characterized by a papule or pustule formation, 24-48 h after sterile-needle prick. It is affected by a wide array of factors, including the physical properties of the needles being used, number of pricks and disease related factors such as male gender, active disease. There is a great variation in reactivity among different populations with very low positivity rate in regions of low prevalence like Northern Europe, and higher prevalance mainly in communities living along the historical Silk Road, like Turkey, China and Middle Eastern countries. SPR is not constant during the disease course, has lost its sensitivity over decades and can be positive in various disorders including Sweet's syndrome, pyoderma gangrenosum, Crohn's diesease, A20 haploinsufficiency, deficiency of IL-1-receptor antagonist and few others. Nevertheless, it is a criteria included into many currently used diagnostic or classification criteria for Behcet's disease. Although, not being fully uncovered yet, available data points to the activation of both innate and adaptive immune system with an inflammatory response mediated by polymorphonuclears and T-cells. In addition to its utility in diagnosis of Behcet's Disease, SPR may serve as a model for investigating the inflammatory pathways involved in the etiopathogenesis of this complex disease.
Keywords: intraepidermal pustule; Behcet's disease; Th1 response; skin pathergy reaction; cutaneous innate immune response; BEHCETS-DISEASE; SKIN HYPERREACTIVITY; MANIFESTATIONS; PATHOGENESIS; INVOLVEMENT; CRITERIA; NEEDLES; LESIONS